Meningkatkan Karakter Tanggung Jawab Belajar Siswa dengan Menggunakan Media Permainan Ular Tangga Pada Mata Pelajaran Matematika di Sekolah Dasar - Y Yantoro; Devi Liansari (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2016)
The purpose of this study was to determine the increase in the character of student learning responsibilities by using snake ladder game media in class III mathematics subjects at SD Negeri 13/1 Bulu. This research method is class action research. In this research has three cycles, in one cycle carrying out two meetings. The procedures of this research are four, namely planning, implementation, observation and reflection. The results of this study showed that in the first cycle teacher activity reached 66.66%, student activities in playing snakes and ladders reached 66.66% and student learning responsibilities in this cycle reached 50.66%. while the second cycle of teacher activity reached 100%, student activity in performing snake play ladder 88.88%, and student learning responsibilities 68.96%. in the second cycle it has experienced an increase but has not reached the established criteria. Then continued in the third cycle with the percentage of teacher activity 100%, student activity 100% and student learning responsibilities have reached 81.8%. Based on the results of the research, it can be concluded that the use of snake ladder game learning media in the eyes of third grade mathematics learning at SDN 13/1 Muara Bulian can improve the character of student learning responsibilities.